Sculpting Knowledge: Black Methodologies, Education Research, and Citation as Method-Making - Wilson Kwamogi Okello; Tiffany M. Nyachae; DeMarcus A. Jenkins (International Journal of Qualitative Methods)
Centering Blackness in educational research is a pursuit of liberation grounded in process, inquiry, and relational praxis. This approach recognizes liberation as an ongoing, unfinished endeavor, urging researchers to disrupt the normative systems that constrain Black life and knowledge. Black methodologies emerge as flexible and transformative, drawing on Black creative and intellectual labor to challenge dominant epistemologies. In this context, centering Blackness involves using citation as a method-making practice—a critical approach to knowing, relating, questioning, and imagining otherwise. The articles in this collection embody these principles. Together, they advocate for referential, relational, and rebellious approaches to knowledge, expanding the possibilities of research rooted in Blackness. This collection reorients educational inquiry by proposing Black living as a method to rethink, disrupt, and transform systems of knowledge and power.